2018
DOI: 10.1111/bjd.17023
|View full text |Cite
|
Sign up to set email alerts
|

Can antibiotics be harmful in atopic dermatitis?

Abstract: Linked Article: Harkins et al. Br J Dermatol 2018; 179:951–958.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…34 All of these can aggravate already inflamed skin, and in several studies the use of antimicrobials and medicated shampoos has been found to be beneficial in combination with other treatments for AD, 37,38 however, there is concern about increasing resistance of bacteria with the continued use of antibiotics. 39 As with epidermal barrier dysfunction, changes in microbiota community diversity and prevalence might be primary or secondary to AD development.…”
Section: Immunopathologymentioning
confidence: 99%
“…34 All of these can aggravate already inflamed skin, and in several studies the use of antimicrobials and medicated shampoos has been found to be beneficial in combination with other treatments for AD, 37,38 however, there is concern about increasing resistance of bacteria with the continued use of antibiotics. 39 As with epidermal barrier dysfunction, changes in microbiota community diversity and prevalence might be primary or secondary to AD development.…”
Section: Immunopathologymentioning
confidence: 99%
“…In essence, resistant strains to decolonization by fusidic acid and mupirocin are increasingly reported [152]. As a consequence, the lack of therapeutic efficacy with the emergence of these resistant strains has underscored the importance of avoiding the long-term use of topical or systemic antimicrobial in AD [153].…”
Section: Admentioning
confidence: 99%
“…The use of topical antibiotics for skin infections is not a new concept, and common antibiotics such as mupirocin are regularly used for skin infections caused by staphylococci. Skin diseases associated with S. aureus colonization including atopic dermatitis (AD) often use this treatment method as colonization with this species results in disease exacerbation and skin barrier dysfunction ( 39 41 ). Antibiotics have been shown to decrease the severity of AD, however, there are increasing reports of antimicrobial resistance in S. aureus strains isolated from patients with AD ( 42 44 ).…”
Section: Current Treatment Options For Ak and Csccmentioning
confidence: 99%